(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The primary objective of this thesis is to find the worth and influence of digital marketing on the competitive setup of startup companies. It would further be analyzed whether it positively influences the development of a startup company, brand recognition, meets consumer loyalty, and strengthens its relationships with customers. This concept has not been researched on before. The only Study we could find related to this is the correlation between social media and innovation in startups which itself shows that social media positively affects innovation in startup companies. Qualitative research methodology has been adopted for the study, and the data is gathered basically from semi-structured interviews with five startup firms. Secondary sources that were used in this research are peer-reviewed articles and journals and some websites. The Study concludes that digital marketing is acknowledged as a creative and efficient method of achieving, maintaining, and establishing the relationship with the customers. Out of all, online channels and platforms, such as websites, industry-specific outlets, and forums, have been found the most beneficial to startups. It also suggests a new startup can grow significantly through digital marketing, creating brand awareness, building trust, and building consumer awareness. Most of the startup organizations fail to adopt digital marketing strategies in the early stages of their organization’s establishment. Our studies would help other start-ups to consider digital marketing for their marketing strategy. Recommendations for further study a related but more detailed study in the state of Madhya Pradesh and a study in a central state of the country.